A ostra se abriu : percepções de alunos surdos sobre seu processo de aprendizagem de língua inglesa em um curso a distância - Xavier, Priscila Aparecida Moraes Henkemaier (2014)
Deaf education has transformed significantly over the last thirty years, with key achievements as acceptance of bilingualism as an ideal condition for effective education of the deaf. Since 2006 Language Sign Languagecoursehasestablished, one of the recent achievements in the area, linguistic discussions have increased expanding both theoretical and practical knowledge about language, and the deaf’sability to acquire different languages. Considering this scenario , this work is based onthe context in which the concept of literacy must include the Multiliteracies and Critical Literacy perspectives (PERREIRA, 2011; ROJO, 2009; JORDÃO; 2011; CARBONIERI, 2012) in order to expand students ' critical thinking, providing space for reflections about themselves and about the world where they live. It aims to analyze what are the meanings produced by a group of deaf students at an English course in distance education,adding to these analysis discussions about foreign language education for the deaf and the teaching method itself. The study has support in theoretical studies Perreira (2011) , Rojo (2009), Sousa (2008) and Aragão& Borba(2012) about the concept of multiculturalism, critical literacy and Jesus(2008 ) on the implications of distance education , new technologies and multiliteracy. The questions that led the research were the following: 1) How can you see the deaf students learning process in English in the distance education? 2)What are the contributions of the distance teaching modality in written English teaching and learning process for deaf students? (especially in relation to strategies and options to foster multiliteracy). The research methodology had an interpretive approach starting with critical descriptions, since the particular experience of the researcher (as deaf and English learner in different courses)to the corporate experience as a teacher of distance English course for deaf people. The data are generated by questionnaires, from the developed activities along the course, questions, interactivity and interviews with participants. The results suggest the need for teaching strategies which take the concept of image as fundamental in teaching English to deaf, but realizing that " image " is not the picture that accompanies the activities , but the visual structure of text presentation in relation to its syntax.